2020
DOI: 10.1002/ijfe.2383
|View full text |Cite
|
Sign up to set email alerts
|

The impact of macro economy on the oil price volatility from the perspective of mixing frequency

Abstract: In this paper, GARCH-MIDAS model is used to study the influence of macro economy, including the levels and volatilities of macroeconomic variables, on the price fluctuations of crude oil market during the period from 1990 to 2018.The results indicate that, for the levels of macroeconomic variables, economic growth, inflation and total export-import volume have significant negative impacts on oil fluctuations. However, exchange rate has a significant positive impact on oil volatility. And short-run interest rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…However, COVID-19's effects on the energy and stock markets are slightly different than those of the GFC, EDC, and GCS. The three latter events were initiated by a specific negative event (e.g., the Lehman bankruptcy in 2008), and then the shock was transmitted to the whole financial market ( Gong, Wang, & Shao, 2020 ; ( Saeed & Ridoy, 2020 ) Shehzad, Xiaoxing, & Kazouz, 2020 ; Shibata, 2020 ). COVID-19, meanwhile, was initially underestimated, and financial markets were not seriously affected at first.…”
Section: Introductionmentioning
confidence: 99%
“…However, COVID-19's effects on the energy and stock markets are slightly different than those of the GFC, EDC, and GCS. The three latter events were initiated by a specific negative event (e.g., the Lehman bankruptcy in 2008), and then the shock was transmitted to the whole financial market ( Gong, Wang, & Shao, 2020 ; ( Saeed & Ridoy, 2020 ) Shehzad, Xiaoxing, & Kazouz, 2020 ; Shibata, 2020 ). COVID-19, meanwhile, was initially underestimated, and financial markets were not seriously affected at first.…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). However, the effects of COVID-19 on energy commodities and stock markets are slightly different from other financial crises such as the GFC, EDC, and CSC, which all originated from a particular point due to a particular negative event, such as the Lehman bankruptcy in 2008, then transferred shocks to the overall financial markets (Gong et al. , 2020; Jeris and Nath, 2020; Shehzad et al.…”
Section: Review Of Literaturementioning
confidence: 95%
“…Existing research suggests that the GFC and COVID-19 are similar, to some extent, because both have had serious, long-lasting impacts on the economy (Jebabli et al, 2022;Zhang et al, 2021). However, the effects of COVID-19 on energy commodities and stock markets are slightly different from other financial crises such as the GFC, EDC, and CSC, which all originated from a particular point due to a particular negative event, such as the Lehman bankruptcy in 2008, then transferred shocks to the overall financial markets (Gong et al, 2020;Jeris and Nath, 2020;Shehzad et al, 2020;Shibata, 2021). In the beginning, COVID-19 was underestimated, and did not affect the financial markets.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, many indicators determine oil price volatility. In this regard ( Gong et al, 2020 ), identified that total export-import volume, inflation, and economic growth have a significant negative effect on the volatility of oil prices. That is, these indicators reduce oil price volatility.…”
Section: Literature Reviewmentioning
confidence: 99%